Effects of adding EM bacteria and mechanical aeration on water quality, growth and antioxidant status of Meretrix meretrix and Exopalaemon carinicauda farmed in the clam–shrimp polyculture system. (10th December 2021) - Zhang, Zhidong; Wu, Yangping; Zhang, Yu; Cao, Yi; Chen, Suhua; Tian, Zhen; Li, Qiujie; Sun, Xuefeng; Chen, Aihua
Abstract: In coastal China, the clam–shrimp polyculture system is a new model of seawater aquaculture. A 60‐day rearing experiment was performed to evaluate the effects of commercial effective microorganisms (EM) bacteria liquid, containing bacillus, photosynthetic bacteria and lactic acid bacteria and mechanical aeration on water quality and their growth performance and antioxidant status. A 2 × 2 layout was designed, including four treatment groups were abbreviated as O (non‐supplementation of EM bacteria liquid and no mechanical aeration), A (supplementation of EM bacteria liquid), B (mechanical aeration) and AB (supplementation of EM bacteria liquid and mechanical aeration). AB group had significantly lower concentration of ammonia, nitrite, nitrate, total inorganic nitrogen (TIN), total inorganic phosphorus (TIP) and chemical oxygen demand (CODMn ) than O group ( p  < 0.05) on the 60th day. Clams and shrimps farmed in the interaction group (AB group) had significantly higher body weight than O group on the 60th day ( p  < 0.05). Furthermore, body weight of clams had no significant differences between single factor groups (A and B groups) and O group ( p  > 0.05), while shrimps had significantly higher body weight in single factor groups (A and B groups) than O group on the 60th day ( p  < 0.05). Weight gain and specific growth rate of clams had no significant differences among different groups at the same time ( p  > 0.05). Shrimps reared in B and AB groups showed significantly higher T‐SOD activities, T‐AOC and CAT activities than those reared in O and A groups ( p  < 0.05). There were significantly lower MDA activities in B and AB groups than O group ( p  < 0.05), while no significant difference was observed in hepatic MDA activities in A group than other groups ( p  > 0.05). There were no significant differences in T‐SOD activities of clams between the four groups ( p  > 0.05). Clams farmed in AB group had lower MDA activities than other groups ( p  < 0.05). Clams farmed in AB group had significantly higher T‐AOC activities than O and B groups ( p  < 0.05). Although B group in T‐AOC activities was significantly lower than A group ( p  < 0.05), it had no significant difference than O group ( p  > 0.05). Finally, clams farmed in A and AB groups had significantly higher CAT activities than O group ( p  < 0.05), while they had no significant difference than B group ( p  > 0.05). In conclusion, single EM bacteria addition or mechanical aeration had limited function in improving water quality, growth performance and antioxidant capacity of clams and shrimps. In contrast, the interactive impact of adding EM bacteria and mechanical aeration could be competent for this task. Therefore, combined adding EM bacteria and mechanical aeration should be an effective way to improve water quality and their growth performance and immune function in the clam–shrimp polyculture system.